Diversifying or Reinforcing Science Communication? Examining the Flow of Frame Contagion Across Media Platforms. (March 2020) - Jones-Jang, S. Mo; Hart, P. Sol; Feldman, Lauren; Moon, Won-Ki
This study investigated whether increased technological affordances, characterized by the rise of social media, diversified communication in climate change discourse. Extending the literature of intermedia agenda setting, this study examined agenda and frame contagion across Twitter and online news media. Using a large dataset of media content about climate change, time-series analysis showed that news media played a major role in setting agendas and frames, but Twitter has increased its dominance in climate change discussions. The findings address both opportunities for strategic science communication and challenges resulting from unverified scientific claims (e.g., hoax frames) spread on social media.